Asymmetric Effect of Renewable Energy Generation and Clean Energy on Green Economy Stock Price: A Nonlinear ARDL Approach - Avazkhodjaev Salokhiddin Shakhabiddinovich; Noor Azuddin bin Yakob; Lau Wee Yeap (International Journal of Energy Economics and Policy, 2022)
This paper examines the asymmetric impact renewable energy generation and clean energy prices on green economy stock prices by employing monthly data for all three indices end on 2021M07, and start on 2010M12. The nonlinear ARDL approach (NARDL) is applied in order to find short-run and long-run asymmetries. The empirical results indicate that renewable energy generation significant negative impact on green economy stock prices. For the clean energy prices have a positive and negative significant impact on green economy stock prices in selected markets under concern. The short-run coefficients of clean energy stock prices have a significant positive affect on green economy stock prices. The Wald test results confirmed the green economy stock price adjustment is running towards the long- and short-run steady increment regarding positive and negative shocks in renewable energy generation and clean energy. Finally, the dynamic multipliers showed that prices of renewable energy generation have a positive (negative) impact on green economy stock prices. Indeed, clean energy prices respond quickly to the changes (both positive and negative) on green economy prices in all selected markets. In sum, the negative shocks dominate positive shocks in renewable energy generation and clean energy, and results indicate that a positive and negative relationship was noted between these covariates and green economy stock prices.